Optimization of the structure of diesel-generator units of ship power system - Mahmoud, Mohammad Salem Al-suod; Ushkarenko, Alexander O.; Dorogan, Olga I. (My University, 2015)
The study proposes the algorithm for selecting the optimal values of rated power generating units, based on the statistical processing of information about the daily workings of the energy generators accumulated software top-level automated control system (ACS) power plant. The calculated nominal capacity can be used to select the diesel-generator units when upgrading the ship power station.
Mahmoud, Mohammad Salem Al-suod. Optimization of the structure of diesel-generator units of ship power system / Mohammad Salem Al-suod. Mahmoud, А. О. Ushkarenko, О. І. Doroga // International Journal of Advanced Computer Research. – March 2015. – Vol. 5, іss. 18. – P. 68–74.
Keywords: diesel-generator; ship power station; state chart; simulation; optimum unit commitment